Multilevel mixed effects analysis of individual and community level factors associated with modern contraceptive use among married women in Uganda - Ronald Wasswa; Allen Kabagenyi; Paulino Ariho (BMC, 2021)
Abstract Background In spite of the universal right for women to decide freely for themselves when, and how many children they want to have in life, married women in Uganda are less likely to use modern contraceptives as compared to other marital categories. This study examines the individual and community factors associated with modern contraceptive use among married women in Uganda. Methods The study used data from the 2016 Uganda Demographic and Health Survey which comprised of 8671 married women aged 15-49 years who were fecund and non-pregnant at the time of the survey. Analysis was done using a multilevel mixed-effects logistic regression model. Results Findings showed that married women who were; Muslims (AOR = 0.78, CI = 0.66-0.91), had more than five children (AOR = 0.76, CI = 0.61-0.98), staying in communities with high poverty (AOR = 0.78, CI = 0.65-0.93), with older age at first birth (AOR = 0.94, CI = 0.92-0.96) as well as having spousal age difference of more than 9 years (AOR = 0.86, CI = 0.76-0.98) were associated with low modern contraceptive use. Women living in communities with higher age at first marriage (AOR = 0.93, CI = 0.88-0.98) or higher sexual debut (AOR = 0.91, CI = 0.85-0.98) were also associated with reduced odds of modern contraception. In addition, older women (AOR = 1.03, CI = 1.01-1.04), having secondary/higher education (AOR = 1.93, CI = 1.58-2.37), living in a rich household (AOR = 1.32, CI = 1.14-1.53), short distance to health facility (AOR = 1.18, CI = 1.06-1.31), high community education (AOR = 1.38, CI = 1.17-1.62), high community exposure to family planning messages (AOR = 1.24, CI = 1.08-1.42), and communities with high proportion of women working (AOR = 1.22, CI = 1.06-1.39) were more likely to use modern contraceptives. Conclusion The study revealed that both individual and community factors were important in explaining the factors associated with modern contraceptive use among married women in Uganda. Therefore, there is need to invest in community based programs like: family planning outreach services, mass media campaigns and community mobilization activities to help in dissemination of family planning information, increase awareness and promotion in use of modern contraceptives. Also, expansion of higher education and the need to make family planning services available and accessible to areas with limited physical access to health facilities will lead to sustained increase in uptake of modern contraceptives.